A Study of Drinking Water Properties in Some Hospitals in Baghdad City - Al Fatlawy, Yaaroub Faleh Khalef; Kadhim, Faiza; Mahdii, Beadaa Abdalqader (Iraqi Journal of Science, 2024)
One of the bigger problems in drinking water is disinfection by-products (DBPs) that come from chlorinated disinfection. This study’s goal was to evaluate the drinking water in Al-Yarmouk Teaching Hospital, Ibn Sina Hospital and Ibn-Al-Nafis Hospital.  Samples were collected between October 2018 and September 2019. Physical and chemical characteristics of the water were studied, including (temperature, hydrogen ion (pH), total dissolved solids (TDS), electrical conductivity (EC), turbidity, free residual chlorine, total organic carbon (TOC), total trihalomethanes (THMs), total halo acetic acid (THAAs)). Data analysis showed the highest value of study temperature, pH, TDS, EC, turbidity, free residual chlorine and TOC which was 37oC, 8.4,790 mg/l, 1251 µS/cm-1, 15 NTU, 1.7 mg/l, and 6.7 mg/l  respectively. Total trihalomethanes (THMs) results of drinking water samples from different sites showed that the highest value was 129.6 µg/l in Ibn Sina Hospital during summer while the lowest value was 41.3 µg/l in Ibn Sina Hospital in winter. The results of total halo acetic acid (THAAs) of drinking water sampled from different sites showed that the highest value of 72.9 µg/l was recorded in the sample collected from Ibn Sina Hospital during summer and the lowest THAAs water content of 40.2 µg/l was obtained in the sample collected from Ibn-Al-Nafis during winter. The results of this research were acceptable and within the range of Iraqi standards.